1985
DOI: 10.3168/jds.s0022-0302(85)80926-7
|View full text |Cite
|
Sign up to set email alerts
|

Mammary Blood Flow and Regulation of Substrate Supply for Milk Synthesis

Abstract: In ruminants, mammary supply of substrate varies with rate of mammary blood flow and concentrations of blood substrates. Blood concentrations of most mammary substrates, except acetate and tryptophan, do not vary greatly with feed intake, short term. Fasting reduces mammary blood flow, whereas milking and injection of growth hormone or thyroxine increase flow. It is proposed that the fraction of cardiac output that perfuses the udder of lactating ruminants plays a role in regulation of nutrient partitioning be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
65
0
2

Year Published

1994
1994
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(70 citation statements)
references
References 113 publications
3
65
0
2
Order By: Relevance
“…The quantity of blood irrigating the udder results from complex regulatory mechanisms, depending both on the partitioning of cardiac flow between different tissues in the body and local regulation which allows a given organ to adjust its arterial nutrient flow to its level of metabolic activity. In lactating cows, 15-16% of the cardiac output is delivered to the udder and whole mammary blood flow averaged 7 L.min −1 in cows producing 16 kg of milk daily [13]. The udder's efficiency to extract glucose from blood plasma is relatively poor; the glucose extraction rate (arteriovenous difference in glucose concentrations divided by the arterial glucose concentration) is on average 26% [14,15] and can fall to 15% in dairy cows [16].…”
Section: The Mammary Utilisation Of Glucosementioning
confidence: 99%
See 2 more Smart Citations
“…The quantity of blood irrigating the udder results from complex regulatory mechanisms, depending both on the partitioning of cardiac flow between different tissues in the body and local regulation which allows a given organ to adjust its arterial nutrient flow to its level of metabolic activity. In lactating cows, 15-16% of the cardiac output is delivered to the udder and whole mammary blood flow averaged 7 L.min −1 in cows producing 16 kg of milk daily [13]. The udder's efficiency to extract glucose from blood plasma is relatively poor; the glucose extraction rate (arteriovenous difference in glucose concentrations divided by the arterial glucose concentration) is on average 26% [14,15] and can fall to 15% in dairy cows [16].…”
Section: The Mammary Utilisation Of Glucosementioning
confidence: 99%
“…This harmful effect on milk yield was principally due to a lower nutrient flow into the udder, related to a 40 to 70% reduction in the mammary blood flow [41][42][43][44]. In the cow, the mammary blood flow was shown to be halved after fasting for 24 h, and only returned to normal 10 to 12 h after feeding restarted [13]. Similarly, Lough et al [45] observed a 5.1 to 4.3 L.min −1 reduction in the mammary blood flow during a 70% restriction of feed.…”
Section: Arterial Flow Of Glucose In the Mammary Glandmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that cardiac output and total volume of systemic blood flow increased significantly during lactation and late pregnancy compared to dry or early pregnancy periods and these increases may well be associated with increasing milk yields and foetal development, respectively (Davis & Collier, 1985;Olsson et al, 2001;Pourjafar et al, 2011;Zarifi et al, 2012). Furthermore, lactation and parturition challenge the homeostatic mechanisms of ruminants, especially those controlling the cardiovascular system, and blood flows to the udder and uterus are directly related to milk production and gestational age, respectively (Davis & Collier, 1985;Olsson et al, 2001;Zarifi et al, 2012). However, it has been documented that the heart size is not influenced by milking and pregnancy status in dairy goats (Olsson et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…O tratamento com somatotropina eleva a síntese de proteínas de vacas em lactação através de uma melhora da eficiência na utilização de aminoácidos (DAVIS & COLLIER, 1985). Durante balanço energético negativo, o bST reduz a oxidação de aminoácidos como fonte de energia nos tecidos, pois isto aumenta a mobilização de lipídios e acentua o metabolismo da glicose, assim, os aminoácidos poderão ser utilizados para o desenvolvimento e crescimento dos demais tecidos e para a síntese de proteínas no leite (GÜLAY & HATIPOGLU, 2005).…”
Section: Efeito Da Somatotropina No Metabolismo De Carboidratos Lipíunclassified